2015
DOI: 10.1016/j.brs.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrode Drift in Transcranial Direct Current Stimulation

Abstract: Background Conventional transcranial direct current stimulation (tDCS) methods involve application of weak electrical current through electrodes encased in saline soaked sponges affixed to the head using elastic straps. In the absence of careful preparation, electrodes can drift from their original location over the course of a tDCS session. Objective The current paper investigates the influence of electrode drift on distribution of electric fields generated by conventional tDCS. Methods MRI-derived finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…Nevertheless, tDCS is a relatively crude method with low spatial specificity. There exist some computational models that can simulate the current flow in the brain (Brunoni et al, 2015;Woods, Bryant, Sacchetti, Gervits, & Hamilton, 2015;Kuo et al, 2013;CaparelliDaquer et al, 2012;Dmochowski, Datta, Bikson, Su, & Parra, 2011), but they need to be verified with experimental methods. In addition, a combination of tDCS and functional imaging can help to better elucidate the neural mechanisms underlying the stimulation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, tDCS is a relatively crude method with low spatial specificity. There exist some computational models that can simulate the current flow in the brain (Brunoni et al, 2015;Woods, Bryant, Sacchetti, Gervits, & Hamilton, 2015;Kuo et al, 2013;CaparelliDaquer et al, 2012;Dmochowski, Datta, Bikson, Su, & Parra, 2011), but they need to be verified with experimental methods. In addition, a combination of tDCS and functional imaging can help to better elucidate the neural mechanisms underlying the stimulation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies monitoring physiological changes following tDCS and computational modeling studies of predicted current flow demonstrate that the relative location of electrodes results in significant differences in where and how much current is delivered to the brain (Minhas et al 2012; Kessler et al 2013b; Woods et al 2015). For example, Nitsche and Paulus (2000) demonstrated that relative differences in electrode locations altered whether or not tDCS impacted TMS generated motor-evoked potentials (MEPs).…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…For example, Nitsche and Paulus (2000) demonstrated that relative differences in electrode locations altered whether or not tDCS impacted TMS generated motor-evoked potentials (MEPs). Numerous modeling studies have demonstrated significant differences between relative locations of electrodes, with results varying from stimulation of the whole brain to more selective stimulation of particular lobes of the brain (Minhas et al 2012; Kessler et al 2013b; Woods et al 2015). Woods et al (2015) further demonstrated that as little as 1cm of movement in electrode position significantly altered the distribution of predicted current flow in the brain, as well as the intensity of stimulation in specific brain regions Computational modeling (discussed in detail in a later section) can be a useful tool for the a priori design of tDCS electrode positions for a given study.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, even a slight (about 5 %) drift of electrodes during stimulation can cause significant change in electric field. (Woods et al 2014) Therefore, current flows may vary substantially, which may cause inconsistent effects between individuals (Horvath et al 2014). The variations of current flow may also be associated with paradoxical stimulation effects, as represented by "cathodal stimulation" and suppressing performance by either anodal or cathodal stimulation (Filmer et al 2013).…”
Section: Introductionmentioning
confidence: 99%